Оптимальне керування гіперболічною системою напівлінійних рівнянь першого порядку з нескінченним горизонтом планування - Дерев'янко, Н.В.; Кирилич, В.М. (Український математичний журнал, 2015)
Установлены необходимые условия для задачи оптимального управления полулинейной гиперболической системой. Сопряженная задача к исходной является полулинейной гиперболической задачей без начальных условий. Предложенный подход основан на использовании специальной вариации непрерывно дифференцированного управления. Доказано существование глобального решения смешанной задачи для полулинейной гиперболической системы в неограниченной по времени полосе. При доказательстве соответствующих теорем использован принцип сжимающих отображений и метрики с весовыми функциями. We establish necessary conditions for the optimality of smooth boundary and initial controls over a semilinear first-order
hyperbolic system. The problem adjoint to the original problem is a semilinear hyperbolic system without initial conditions.
The suggested approach is based on the use of a special variation of the continuously differentiable control. The existence
of global generalized solution of a semilinear first-order hyperbolic system in a domain unbounded in time is proved. The
proof is based on the use of the principle of contractive mappings and a space metric with weight functions.